Reformed teacher training programme supporting the prevention of early school leaving (Training and Practice : Journal of Educational Sciences, 2018)
The concept of Early School Leaving (ESL) is relatively new in Hungary. The proportion of early school leaving was slightly decreasing until 2010, but since then it has been increasing according to KSH (Central Statistical Office). A number of international publications deal with this issue: Schargel, Thacker and Bell (2007); Rumberger, Lim (2008); Lyche (2010). In Hungary extended research is being carried out into the problem: Meleg (2015); Imre (2014); Mihályi (2014); Forgács (2009); Hanák (2016) etc. The questions are whether teacher training is able to promote the prevention of ESL and what short and long term results it can offer. This publication presents and examines a teacher training programme focusing on the prevention of ESL.